Da arte para a arquitetura: dispositivos artísticos contemporâneos como meios de investigação de arquitetura - Roberto Rolim Andres (2008)
This paper investigates possible intersections between architectural practice andsome contemporary artistic modalities, emphasizing the use of art as an experimental field for architecture in which architects can investigate architectural matters. So, it intends to study possible qualifications of architectural practice opened by the use of some contemporary art modalities specially these that use space as support and theme (Installation, Environments, Ambientes, In Situ). Firstly, it approaches the contemporary architectural practice and tries to understand problematic points in its production. It analyzes the visual emphasis of architectural esthetic and the approach of architecture as an object, trying to uncover their relationship with architects procedures and approaches. Then, it analyzes the representation tool a central point on architectural production and discusses its implications and limits as the main tool for architectural design. Then, it analyzes some artistic modalities that surpassed painting and sculpture, working in urban and architectural space. These analysis are made aiming to investigate possible qualifications of architectural practice, based on the discussion above exposed. It points several possibilities of qualifying architecture, what could be effective if architects use these artistic modalities as models for their experimental practice. Some of these points are: to reduce the visual emphasis on architectural esthetic; to emphasize the internal spatiality of architecture (which articulates peoples relationship), instead of the architectural object; to assume that concrete reality interferes with the ideas about architecture, eliminating the platonic concept of transcription between ideas and forms; to assume that the world must to be a dialogical support of architecture, and that it is not passive or neutral. Finally, some educational and practical experiences are related, aiming to contextualize it with the discussion above exposed. Then, it points the importance of some contemporary art modalities as experimental fields for architectural practice and theory. It concludes making the relationship of some problems related on architectural practice and some procedures inherited from modern science. It points the importance of surpassing the ideas of objectivity and spiritual transcendence, aiming to approach the human being in his real position: inside the world, and which worlds perception involves all the body.